Habilidades sociais educativas do professor e sua relação com a avaliação de alunos que sofrem, praticam e testemunham o bullying - Ponti, Franciele da Silva Del (2020)
Bullying represents a social and public health problem, which requires the development of strategies for remedial and preventive intervention of the phenomenon in schools. Since in Brazil bullying occurs more frequently in the classroom, the role of the teacher in combating this phenomenon stands out. There is a scarcity of studies in the literature analyzing the phenomenon from the point of view of the teacher's social educational skills, particularly from the perspective of those involved in bullying. The aim of the study was to investigate relationships between the educational and social skills self-attributed by teachers with those attributed to their teachers by students who practice, suffer or witness. The sample consisted of 242 students and their respective Portuguese language teachers (N = 8). The instruments answered by the teachers were: nine complementary HSE questions related to bullying extracted from the Portfolio of Del Prette and Del Prette (2017) and the reduced version of the Social Educational Skills Inventory (IHSE-Prof) with only potentially anti-bullying questions. With students, these two instruments were used, but adapted to refer to the student's assessment of the teacher's performance. The students also answered the School Violence Scale (EVE), which made it possible to classify the sample in 25 students as victims and 11 as aggressors, 13 “victim-aggressor” students and 193 witnesses. The female gender was considered a condition of greater vulnerability for all classifications. Teachers' self-assessments at IHSE-Prof were predominantly better than those received by students. In the Complementary Items according to the students, the most frequent educational actions of the teachers refer to the handling of discipline. The teachers’ assessments in IHSE were more similar to the group of aggressors in terms of frequency and effectiveness. Among the groups of students involved in bullying, there was no significant difference, mainly in the F1 scores, in mediation of learning and development. The results suggest a reflection on the role of the teacher's HSE to the reduce the phenomenon, in addition to showing that differences between the subgroups in the way they evaluate the teacher's educational actions. Additionally, the data show differences in the way teachers deal with these students and/or how they are perceived and the importance of considering the evaluation of students involved in bullying, suggesting new perspectives in combating bullying at school, based on the teachers' educational social skills. Future research may focus on increasing the existing knowledge about the specifics of the groups to increase the effectiveness of interventions.